Freedom, a history - Treadgold, Donald W., 1922-1994 (New York University Press, 1990)
A worldwide trend toward democracy is surely one of the more remarkable phenomena of our times, even if the movement twoard that goal may often be haphazard and elusive. Past history will provide a healthy skepticism concerning the likelihood of democracy being reached in the near future in many parts of the world, as well as a preparedness for the possibility that many countries apparently close to the "institutional divide" are going to slip back rather than cross it soon. Nevertheless, the past 2600 years, or even 5000, yield the reassuring message that during that long period freedom has improved its extent significantly, with respect both to geographical breadth and institutional depth.This book is the first to attempt to describe the history of the growth of freedom on a world scale within one single set of covers. It sets out not to redefine freedom nor to discvoer freedom where no one else has, nor to argue that freedom is the proud possession of one country or tradition or people. Its purpose instead is to show how certain elements of free society made their appearance in an amazing variety of places, from ancient Sumeria and China to medieval Japan, modern Czechoslovakia and Costa Rica, in areas both inside and outside of the Western European and North American tradition that will probably be familiar to most readers of the English language edition of this book.The whole story, with its fits and starts, triumphs and tragedies, deserves the thoughtful reflection of everyone who in the wish to establish and protect freedom would avoid needless disappointment and despair and desires to act intelligently to attain the attainable. But even for the quietest, the person who has no faith in human action to improve man's lot, the story is worth pondering, for along with failure and misery it holds much that is noble and uplifting, tells of much gain for humanity through patient suffering and self-sacrifice, and catches a vision of liberty for all in the present an dpossible future that was inconceivable at the dawn of history.